Ekologiczny wymiar dobra wspólnego w świetle encyklik społecznych papieży posoborowych - Zagończyk, Dorota (Seminare. Poszukiwania naukowe, 2022)
During the last thirty years ecological challenges have become a vital problem. They were mentioned as an important issue in the social encyclicals of the Popes of the period (John Paul II, Benedict XVI). The popes pointed out the need for a redefinition of the concept of common good, which was understood as a set of conditions conducive to comprehensive development of man and society. The common good is a universal value including all the good and concerning every human being. The common good can be achieved in the conditions of peace and in such living conditions which do not outrage human dignity. The environmental dimension of the common good is understood as life, natural environment and ecological ideas. The highest value is life, thanks to which everyone can fulfill his vocation to the full development only by realizing the common good.